Mathematical Model of the Process of Transportation of Construction Goods by Automobiles - Muratov Abobakr Kholikberdievich (Genius Journals, 2023)
A study of construction shipments to customers by means of Motor Vehicles shows that each sender carries out transportation on the basis of their own interests, not taking into account the interests of other senders, especially the population in the service sector. This leads to overuse of vehicles and, accordingly, to an increase in the cost of delivery of cargo. The article aims to increase the efficiency of transportation by applying mathematical methods to the delivery of their cargo to the destination
Keywords: automobile; construction cargo transportation; mathematical model